Ultimate composition analysis of municipal solid waste in Muscat. (1st April 2017) - Baawain, Mahad; Al-Mamun, Abdullah; Omidvarborna, Hamid; Al-Amri, Wala
Abstract: Properly uncontrolled municipal solid wastes (MSWs) may affect public health and the environment. This study investigates the ultimate composition of the MSWs in Muscat, Oman. To achieve this, a set of 22 solid and leachate samples was collected in February 2015. The solid samples were screened according to their size fractions from less than 8 mm up to 100 mm. In addition, the fresh and old leachate samples were examined as well. The ultimate analyses were conducted for various physical and chemical characteristics of the MSW samples, e.g., composition of waste, moisture content (MC), volatile content (VC), loss on ignition, total oxides, elemental analysis, chemical content, heating value and energy content. Moreover, the leachates were analyzed for pH, electrical conductivity (EC), turbidity, total solid (TS), bacteriological analysis, biochemical oxygen demand (BOD), chemical oxygen demand (COD), total organic carbon (TOC), ammonia nitrogen, sodium and potassium, and major anions. From the study, it was found that more than 43% by weight of the disposed materials at the landfill consisted of biodegradable organic compounds. The results also showed that the main components of the total generated wastes were plastic wraps (24%), cardboard (14%) and food wastes (8%). This study also recommends a "waste-to-energy" program, because of the high-energy content of the MSWs (>15, 000 kJ/kg). The chemical formulas of the MSW were obtained as C215 H395 O120 N2 S with sulfur and C125 H230 O70 N without sulfur element. Highlights: Ultimate analyses were conducted on the MSW samples in Muscat, Sultanate of Oman. Biodegradable organic compounds contain more than 43% of the disposed materials. Chemical formulas for the MSWs were proposed. The MSW has a potential to generate more than 15, 000 kJ/kg of energy.